An evaluation of internship program by using Kirkpatrick evaluation model - Lathifa Rosiana Dewi; Badrun Kartowagiran (Universitas Negeri Yogyakarta, 2018)
This study was aimed at evaluating an internship program using Kirkpatrick's evaluation program. The subjects of the study were students of batch 2015 and instructors. Slovin formula was used to calculate the sample. A questionnaire and teaching assessment sheet were used as instruments for collecting data. This study used content validity and exploratory factor analysis as the validity of the test. Reliability was estimated by Cronbach's Alpha. The results of this study showed that (1) in facility, the level of satisfaction was in the 'very satisfactory' category (77.01%); (2) in instructor, the level of satisfaction was in the 'very satisfactory' category (82.76%); (3) in schedule, the level of satisfaction was in the 'satisfactory' category (50.57%); (4) in material, the level of satisfaction was in the 'very satisfactory' category (89.66%); and (5) in students' teaching abilities. The improvement was in the 'very satisfactory' category.